Paradoxical Hemodynamic Instability After Pericardial Window. Issue 8 (4th April 2016) - Han, Andrew J.; Slomka, Teresa; Mehrotra, Anurag; Murillo, Luis C.; Alsafwah, Shadwan F.; Khouzam, Rami N.
Abstract : Paradoxical hemodynamic instability (PHI), also called postoperative low cardiac output syndrome (LCOS), is a rare but fatal complication after drainage of a pericardial effusion (PEf). This condition usually develops within hours postprocedure and appears unrelated to the method of drainage. The exact mechanism of this condition is not well understood. We present a case of an 84‐year‐old patient with no previous cardiac or cancer history who presented with acute shortness of breath (SOB). Computed tomography (CT) ruled out pulmonary embolism and echocardiography confirmed early tamponade. Following emergent subxiphoid pericardiectomy, the patient developed hemodynamic instability and shock and subsequent multiorgan failure. Repeat echocardiography revealed left ventricular (LV) hypercontractility and new right ventricular (RV) dilatation with akinesis. The patient's condition continued to deteriorate in spite of maximal doses of pressors. The patient died after the family's request to discontinue further extraordinary measures. Mini‐Abstract: An 84‐year‐old patient with no previous cardiac or cancer history presented with acute cardiac tamponade. Following emergent pericardial window, the patient developed hemodynamic instability with shock and multiorgan failure. Repeat echocardiography revealed left ventricular hypercontractility and new right ventricular dilatation with akinesis.